EVALUASI PROGRAM PENGUJIAN KENDARAAN KELILING OLEH DINAS PERHUBUNGAN KOTA DENPASAR - Yoni Enjels, Ni Kadek; Winaya, I Ketut; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2020)
ABSTRACT   The Denpasar City of Department of transportation is one of the institutions in Bali Province that apply the testing transportation using pick-up service system. The application of a this system a is aimed to a make a easier a for the a people a to test a their vehicle a and a reduce the traffic jam in technical implementation unit. The innovation of this program begun in 2016.However, in its application there a are a still a problems a related a to the lack a of socialization and uneven cars of testing  in Denpasar. This a research a used a qualitative a descriptive a method a the a data a collection a techniques a are a observation,interview and documentation. It is showed from six criterias that used for that system, it still faces some problems for each indicators.Related to the effectiveness of vehicle testing, time efficiency, human resource efficiency, adequacy in overcoming vehicle queue problems and employee responsiveness.   Key words : Evaluation, Service, Testing Transportation Using Pick up Service System